Інтродукція і селекція нетрадиційних плодових рослин в Україні: історія, реалії, перспективи - Klymenko, S.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2008)
Introduction history of many fruit plants is connected with monastery gardens, created in XI century. From monasteries horticulture is spreading on prince and town gardens. From second half of XIX century horticulture is acquiring industrial character, nontraditional cultivars introduced. Great significance in formation of home horticulture had works of outstanding scientists L.P. Simirenko and N.F. Kaschenko. Rich genetic pool of nontraditional fruit plants has been accumulated in the botanical gardens, institutes of horticulture and dendroparks of Ukraine. The role of varieties as the lasting part of introduction and selection and peculiarities of the adaptive fruit growing are described and also the achievements within selection of nontraditional fruit plants in Ukraine. Perspective sorts of these species have been incorporated in the State Register of Plants Varieties of Ukraine.